Detection of irradiation in bivalves through analysis of thermal behavior and liquid crystal structures - Aglugub, Emmylou Conde (2004)
ABSTRACT Food irradiation is a promising means of preservation but despite approval by authorities, it has not yet gained universal acceptance due to safety considerations. Methods for the detection of radiation treatment have been studied to verify compliance with labeling regulations and to enable consumers to make informed decisions regarding food products. This study explored the use of a technique that is more rapid, economical and simple compared to existing methods. Lipids from bivalves that are common in the Philippine market such as tahong, tulya, and halaan were subjected to analysis of thermal behavior through the use of differential scanning calorimetry (DSC), and liquid crystalline properties through optical polarizing microscopy (OPM) to determine if there are changes due to irradiation. It was observed that in all samples, there are marked differences between the phase transition temperatures of lipids from irradiated and untreated specimens, which signifies that DSC can potentially be used to detect irradiation of tahong, tulya, and halaan. Results from OPM were almost the same for lipids from both non-irradiated and irradiated specimens, thus this method cannot be used for detection of radiation treatment in tahong, tulya and halaan.